Anticoagulation therapy and proximal femoral fracture treatment: An update. Issue 8 (August 2016) - Ktistakis, Ioannis; Giannoudis, Vasileios; Giannoudis, Peter V.
Abstract : Hip fractures in the elderly population have become a 'disease' with increasing incidence. Most of the geriatric patients are affected by a number of comorbidities. Coagulopathies continue to be a special point of interest for the orthopaedic trauma surgeon, with the management of this high-risk group of patients a hot topic of debate among the orthopaedic community. While a universal consensus on how to manage thromboprophylaxis for this special cohort of patients has not been reached, multiple attempts to define a widely accepted protocol have been published. Cite this article: Ktistakis I, Giannoudis V, Giannoudis PV. Anticoagulation therapy and proximal femoral fracture treatment: an update. EFORT Open Rev 2016;1:310-315. DOI: 10.1302/2058-5241.1.160034.